2004
DOI: 10.1021/jm030541+
|View full text |Cite
|
Sign up to set email alerts
|

Design, Syntheses and In Vitro Gene Delivery Efficacies of Novel Mono-, Di- and Trilysinated Cationic Lipids:  A Structure−Activity Investigation

Abstract: Structure-activity investigation including design, syntheses, and evaluation of relative in vitro gene delivery efficacies of a novel series of cationic amphiphiles (1-10) containing mono-, di-, and trilysine headgroups are described in CHO, COS-1, and HepG2 cells. Several interesting and rather unexpected transfection profiles were observed. In general, lipid 1 with the myristyl tail used in combination with DOPE as colipid exhibited superior transfection properties compared to (a) the monolysinated analogues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 31 publications
2
51
0
Order By: Relevance
“…Lipoplex size has been suggested to modulate transfection activity, with larger (within limits) lipoplexes being generally more efficient (27,28). Recent experiments showed, however, that lipoplex size by itself does not necessarily directly correlate to transfection efficiency (29,30), and examples now exist in which smaller lipoplexes are more efficient than larger ones (21,31). Therefore, we examined the aggregate sizes of the two C18͞C10-EPC compounds and their lipoplexes.…”
Section: Structure and Phase Behavior Of Cationic Lipid Aggregates Andmentioning
confidence: 99%
“…Lipoplex size has been suggested to modulate transfection activity, with larger (within limits) lipoplexes being generally more efficient (27,28). Recent experiments showed, however, that lipoplex size by itself does not necessarily directly correlate to transfection efficiency (29,30), and examples now exist in which smaller lipoplexes are more efficient than larger ones (21,31). Therefore, we examined the aggregate sizes of the two C18͞C10-EPC compounds and their lipoplexes.…”
Section: Structure and Phase Behavior Of Cationic Lipid Aggregates Andmentioning
confidence: 99%
“…To this end, recently we have designed and synthesized a series of novel cationic lipids with mono-, di-, and tri-lysine head-groups and common hydrophobic anchors. 80 The in vitro gene delivery efficacies of these lipids were compared in CHO, COS-1, and HepG2 cells. This structure-activity investigation revealed that the cationic lipid with a mono-lysine head-group and myristyl tail (DTMLAC, Fig.…”
Section: B Influence Of Head-group Nature and Head-group Chargesmentioning
confidence: 99%
“…1) was designed and synthesized in our on-going structure-activity program in the area of liposomal gene delivery [25][26][27][28][29][30] as a non-glycerol based mono-cationic lipid where the positively charged terminal amine group was separated from the hydrophobic aliphatic tails by a reasonably long spacer arm. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such complex transfection pathway makes rational design of efficient cationic transfection lipids an arduous task. A number of recent structure-activity investigations [21][22][23][24], including our own [25][26][27][28][29][30], have thrown significant new insights into the various architectural elements of cationic lipids necessary for overcoming the above mentioned cellular barriers involved in lipofection process.…”
Section: Introductionmentioning
confidence: 99%